Strategic innovative marketing : 4th IC-SIM, Mykonos, Greece 2015 - Kavoura, Androniki; Sakas, Damianos P.; Tomaras, Petros (Springer proceedings in business and economics., 2017)
This book presents the latest on the theoretical approach of the contemporary issues evolved in strategic marketing and the integration of theory and practice. It seeks to make advancements in the discipline by promoting strategic research and innovative activities in marketing. The book highlights the use of data analytics, intelligence and knowledge-based systems in this area. In the era of knowledge-based economy, marketing has a lot to gain from collecting and analyzing data associated with customers, business processes, market economics or even data related to social activities. The contributed chapters are concerned with using modern qualitative and quantitative techniques based on information technology used to manage and analyze business data, to discover hidden knowledge and to introduce intelligence into marketing processes. This allows for a focus on innovative applications in all aspects of marketing, of computerized technologies related to data analytics, predictive analytics and modeling, business intelligence and knowledge engineering, in order to demonstrate new ways of uncovering hidden knowledge and supporting marketing decisions with evidence-based intelligent tools. Among the topics covered include innovative tourism marketing strategies, marketing communications in small and medium-sized enterprises (SMEs), the use of business modeling, as well as reflecting on the marketing trends and outlook for all transportation industry segments. The papers in this proceedings has been written by scientists, researchers, practitioners and students that demonstrate a special orientation in strategic marketing, all of whom aspire to be ahead of the curve based on the pillars of innovation. This proceedings volume compiles their contributions to the field, highlighting the exchange of insights on strategic issues in the science of innovation marketing.